Investigation of the Performance of Digital Mammographic X-Ray Equipment: Determination of Noise Equivalent Quanta (NEQQC) and Detective Quantum Efficiency (DQEQC) Compared with the Automated Analysis of CDMAM Test Images with CDCOM and CDIC Programs - Loos, C.; Buhr, H.; Blendl, C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The purpose of this study was to determine the values for noise equivalent quanta, detective quantum efficiency, modulation transfer function, noise power spectrum, and the values for the parameters for automated CDMAM test phantom analyses required to achieve satisfactory quality of digital mammograms.Materials and Methods: During the course of tests according to PAS 1054 (8 CR and 12 DR systems), test images were made with a test phantom insertion plate containing two lead edges in nearly horizontal and vertical directions. Only original data were processed with a program that was developed at the Cologne University of Applied Sciences (FH-Köln). All equipment systems complied with the requirements regarding visual recognition of gold-plated mammo detail test objects. CDMAM test images were also evaluated using the CDIC (CUAS) and CDCOM (EUREF) programs.Results: CDMAM test images show comparable values for the parameters, precision, sensitivity and specificity. DR systems require about half the dose used for CR systems for similar results. The NEQ values achieved with the dose used for the CDMAM test images show larger scatter ranges. The MTF of the different equipment system types differ significantly from each other.Conclusion: Visual evaluation of CDMAM test images can be replaced by automated evaluation. Limiting values were determined for each parameter. Automated evaluation of CDMAM test phantom images should be used to determine the physical parameter NEQQC. This method is much more sensitive to noise and sharpness influences and has a higher validity than diagnostic methods. Automated evaluation objectivizes testing.
Keywords: mammography; image processing; noise equivalent quanta; modulation transfer function; system power; CDMAM